Poster presentation Valorisation of lupanine: Bioprocess development for the removal of a toxic alkaloid from industrial wastewater - Vasquez Christodoulou, Marlen (My University, 2026)
Parmaki S, Vyrides I, Vasquez M, Mota A, Teixeira R, Ferreira F, Afonso C, Drouza C, Koutinas M Valorisation of lupanine: Bioprocess development for the removal of a toxic alkaloid from industrial wastewater, poster presentation, XENOWAC II Challenges and solutions related to xenobiotics and antimicrobial resistance in the framework of urban wastewater reuse, Limassol, Cyprus, 10-12 October 2018.